Triazine-Based Conjugated Microporous Polymers With Different Linkage Units for Visible Light–Driven Hydrogen Evolution - Sheng, Qiannan; Zhong, Xiujuan; Shang, Qianqian; Dong, YunYun; Zhao, Jinsheng; Du, Yuchang; Xie, Yu (Frontiers in Chemistry, 2022)
Conjugated microporous polymers (CMPs), as a kind of two-dimensional material, have attracted extensive attention due to their advantages in visible-light-driven photocatalytic splitting of water for hydrogen evolution. However, improving the microstructure and electronic structure of the material to enhance their photocatalytic performance for hydrogen evolution remains a challenge. We designed and reported two analogous CMPs including CMP-1 and CMP-2 that contain triazine and dibenzothiophene-S, S-dioxide units, which were prepared by Pd-catalyzed Suzuki-Miyaura coupling reaction. The main difference of two CMPs is that the triazine units are connected to benzene unit (CMP-1) or thiophene unit (CMP-2). Both of the CMPs exhibit excellent light capture capability, and compared with CMP-2, CMP-1 has faster separation rates and lower recombination rates for the charge carriers (electron/hole), and then a higher hydrogen evolution rate (HER) was obtained from water decomposition reaction. We find the H2 production rate of CMP-1 can be up to 9698.53 mol g-1h -1, which is about twice of that of CMP-2. This work suggests that molecular design is a potent method to optimize the photocatalytic performance towards hydrogen evolution of the CMPs.